Laguvia manipurensis, a new species of sisorid cat fish (Pisces: Sisoridae) from the Yu River system of Manipur - Arun Kumar, Laifrakpam (Indian Journal of Fisheries, 2011)
A new freshwater sisorid catfish of the genus Laguvia Hora collected from thesoutheastern water bodies of Manipur at Lairok Maru which is drained by theYu river System of Manipur, India is described and illustrated under the nameLaguvia manipurensis. The new species may look similar to Laguvia asperus(McClelland) and Laguvia shawi Hora but can be easily distinguished from theformer by the presence of non-serrated dorsal spine. The new species differs fromthe latter species in having less number of anal and caudal fin rays and differentvalues of morphometric measurements.